Opsonic and Protective Properties of Antibodies Raised to Conjugate Vaccines Targeting Six Staphylococcus aureus Antigens - Pozzi, Clarissa; Wilk, Katarzyna; Lee, Jean C.; Gening, Marina; Nifantiev, Nikolay; Pier, Gerald B. (PLOS ONE, 2012)
Staphylococcus aureus is a major cause of nosocomial and community-acquired infections for which a vaccine is greatly desired. Antigens found on the S. aureus outer surface include the capsular polysaccharides (CP) of serotype 5 (CP5) or 8 (CP8) and/or a second antigen, a β-(1→6)-polymer of N-acetyl-D-glucosamine (PNAG). Antibodies specific for either CP or PNAG antigens have excellent in vitro opsonic killing activity (OPKA), but when mixed together have potent interference in OPKA and murine protection. To ascertain if this interference could be abrogated by using a synthetic non-acetylated oligosaccharide fragment of PNAG, 9GlcNH2, in place of chemically partially deacetylated PNAG, three conjugate vaccines consisting of 9GlcNH2 conjugated to a non-toxic mutant of alpha-hemolysin (Hla H35L), CP5 conjugated to clumping factor B (ClfB), or CP8 conjugated to iron-surface determinant B (IsdB) were used separately to immunize rabbits. Opsonic antibodies mediating killing of multiple S. aureus strains were elicited for all three vaccines and showed carbohydrate antigen-specific reductions in the tissue bacterial burdens in animal models of S. aureus skin abscesses, pneumonia, and nasal colonization. Carrier-protein specific immunity was also shown to be effective in reducing bacterial levels in infected lungs and in nasal colonization. However, use of synthetic 9GlcNH2 to induce antibody to PNAG did not overcome the interference in OPKA engendered when these were combined with antibody to either CP5 or CP8. Whereas each individual vaccine showed efficacy, combining antisera to CP antigens and PNAG still abrogated individual OPKA activities, indicating difficulty in achieving a multi-valent vaccine targeting both the CP and PNAG antigens.